N-type IBC battery and preparation method thereof

By forming an interdigitated n-type doping region and an n-type proto-silicon region on the back of the N-type silicon wafer of the N-type IBC battery, and laser doping is performed on the n-type proto-silicon region, the p-type doping in the prior art is solved. The complex process and many side effects of complex areas have improved the photoelectric conversion efficiency and open circuit voltage of the battery.

CN119230652APending Publication Date: 2024-12-31DAS SOLAR CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310803528.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The p-type doped region of the existing N-type IBC batteries is complex through boron diffusion treatment process and has many side effects, which affects the photoelectric conversion efficiency of the battery.

Method used

After forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of the N-type silicon wafer, an n-type doped region and n-type protosilicon region arranged in interdigitally is formed by laser grooves, and a n-type protosilicon region is formed on the n-type protosilicon region. The boron-containing aluminum coating is laser doped to form a p-type doping region, avoiding the side effects of traditional boron source doping.

Benefits of technology

It improves the photoelectric conversion efficiency of the battery, reduces the emitter contact resistance and dark saturation current, improves the filling factor and short circuit current, and ensures a high open circuit voltage value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230652A_ABST
    Figure CN119230652A_ABST
Patent Text Reader

Abstract

According to the N-type IBC battery and the preparation method thereof provided by the embodiment of the invention, the boron-containing aluminum coating is formed in the first region of the n-type raw silicon region and the laser doping treatment is carried out, so that high-concentration boron doping can be carried out on the n-type raw silicon region to form the p-type doped region; the side effect caused by the doping mode of the traditional tubular boron source is avoided, and the conversion efficiency of the cell is ensured, so that the problems that the forming mode of the p-type doped region of the existing N-type IBC cell is complicated in process and more in side effect, and the photoelectric conversion efficiency of the cell is easily influenced are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to an N-type IBC cell and a preparation method thereof. Background Art

[0002] The interdigitated back contact (IBC) battery is a new type of battery in which the contact electrodes of the P / N junction, substrate and emitter region are made in an interdigitated shape on the back of the battery. Its core technology is to prepare high-quality p-regions and n-regions arranged in an interdigitated shape on the back of the battery.

[0003] The p-type doping region of the existing N-type IBC cell is obtained by boron diffusion treatment, which has a complex process and many side effects, and is likely to affect the photoelectric conversion efficiency of the cell. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an IBC battery and a preparation method thereof, so as to solve the problem that the p-type doped region of the existing N-type IBC battery is obtained by boron diffusion treatment, which has a complex process and many side effects, and is likely to affect the photoelectric conversion efficiency of the battery.

[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing an IBC battery, which comprises:

[0007] After forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of an N-type silicon wafer, laser grooves are formed on the back of the silicon wafer to form an n-type doped region and an n-type original silicon region arranged in an interdigitated manner;

[0008] forming a boron-aluminum coating on a first region in the n-type original silicon region, and then performing a laser doping process on the first region, wherein the first region is used to contact the positive gate line;

[0009] After laser doping treatment, a passivation film layer and an anti-reflection film layer are formed on both sides of the silicon wafer;

[0010] After forming the anti-reflection film layer, a positive electrode grid line in contact with the first region and a negative electrode grid line in contact with the n-type doped region are formed on the back of the silicon wafer to manufacture an N-type IBC battery.

[0011] Furthermore, in the preparation method, the laser marking speed of the laser doping treatment is 32000-38000 mm / s, the power is 550-650 watts, and the frequency is 1000-1500 Hz.

[0012] Furthermore, in the preparation method, a silicon oxide layer and a phosphorus-doped polysilicon layer are sequentially formed on the back side of the N-type silicon wafer, comprising:

[0013] A silicon oxide layer and a polysilicon layer are sequentially formed on the back of an N-type silicon wafer by low-pressure vapor deposition, and then the polysilicon layer is subjected to phosphorus diffusion doping treatment.

[0014] Furthermore, in the preparation method, the sheet resistance of the silicon wafer after phosphorus diffusion doping treatment is 30-40Ω / sq, and the sheet resistance of the silicon wafer after laser doping treatment is 50-60Ω / sq.

[0015] Furthermore, in the preparation method, the passivation layer is an aluminum oxide layer, and the anti-reflection film layer is a silicon nitride layer.

[0016] Furthermore, in the preparation method, before sequentially forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back side of the N-type silicon wafer, the method further comprises:

[0017] performing alkali polishing on the silicon wafer;

[0018] Before forming the boron-containing aluminum coating on the first region within the n-type native silicon region, the method further includes:

[0019] The silicon wafers after laser grooving are chain pickled and texturing treated.

[0020] Furthermore, in the preparation method, the size of the blocks after alkali polishing is 9 to 11 microns.

[0021] Furthermore, in the preparation method, before forming the passivation film layer and the anti-reflection film layer on both sides of the silicon wafer, the method further comprises:

[0022] The silicon wafer after laser doping is pickled.

[0023] Furthermore, in the preparation method, the width of the laser grooving is 250 to 300 microns and the depth is 1.5 to 2 microns.

[0024] The present invention also provides an N-type IBC battery, which is prepared by the above method.

[0025] Compared with the prior art, the embodiments of the present invention have the following advantages:

[0026] In the embodiment of the present invention, after forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of an N-type silicon wafer in sequence, laser grooves are formed on the back of the silicon wafer to form an n-type doped region and an n-type original silicon region arranged in a forked shape; a boron-containing aluminum coating is formed on the first region in the n-type original silicon region, and then the first region is subjected to laser doping treatment; after the laser doping treatment, a passivation film layer and an anti-reflection film layer are formed on both sides of the silicon wafer; after the anti-reflection film layer is formed, a positive electrode grid line in contact with the first region and a negative electrode grid line in contact with the n-type doped region are formed on the back of the silicon wafer to obtain an N-type IBC battery. By forming a boron-containing aluminum coating on the first region of the n-type original silicon region and performing laser doping treatment, the n-type original silicon region can be doped with high concentration of boron to form a p-type doped region, avoiding the side effects caused by the doping method of the traditional tubular boron source, ensuring the conversion efficiency of the battery, and thus solving the problem that the formation method of the p-type doped region of the existing N-type IBC battery is complicated in process and has many side effects, which easily affects the photoelectric conversion efficiency of the battery.

[0027] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of a method for preparing an N-type IBC battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] The applicant of the present invention has found that the current N-type IBC technology route is simply to prepare high-quality P and N regions with interdigitated spacing on the back of the battery. It uses tubular boron diffusion on the original silicon wafer to form the P+ region. Not only is the process complex and costly, but it also has many side effects, which can easily lead to poor photoelectric conversion efficiency of the battery.

[0031] In order to solve the above problems, the embodiment of the present invention provides a method for preparing an N-type IBC battery, which includes steps 101 to 104:

[0032] Step 101, after sequentially forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of an N-type silicon wafer, laser grooves are formed on the back of the silicon wafer to form an n-type doped region and an n-type original silicon region that are arranged in an interdigitated manner;

[0033] Step 102, forming a boron-aluminum coating on a first region in the n-type original silicon region, and then performing a laser doping process on the first region;

[0034] Step 103: after the laser doping treatment, forming a passivation film layer and an anti-reflection film layer on both sides of the silicon wafer;

[0035] Step 104: After forming the anti-reflection film layer, a positive gate line in contact with the first region and a negative gate line in contact with the n-type doped region are formed on the back of the silicon wafer to obtain an N-type IBC battery.

[0036] In the embodiment of the present invention, after forming n-type doped regions and n-type native silicon regions arranged in a forked-finger shape, a boron-containing aluminum paste is printed on the first region of the n-type native silicon region and laser doping is performed, so that the n-type native silicon region can be doped with high concentration of boron to form a p-type doped region, which can reduce the emitter contact resistance and the dark saturation current of the emitter region, and improve the fill factor, short-circuit current and open-circuit voltage, thereby improving the conversion efficiency of the battery. Therefore, the problem that the emitter contact resistance of the p-type doped region of the existing N-type IBC battery is large, resulting in a low open-circuit voltage value of the battery and poor photoelectric conversion efficiency of the battery is solved.

[0037] In the above step 101, an N-type original silicon wafer is taken, and a layer of ultra-thin silicon oxide is formed on the back of the P-type silicon wafer by low pressure chemical vapor deposition (LPCVD) as an ultra-thin tunneling oxide layer, and then a polysilicon layer with a thickness that can meet the passivation effect is prepared on both sides; the thickness can be specifically 100 to 200nm, for example, 150nm. Among them, because the preparation of the polysilicon layer on both sides is conducive to the subsequent removal of the front polysilicon layer, it is not easy to have the two extreme situations of excessive removal or insufficient removal, and the yield is better controlled.

[0038] In the above step 101, after preparing the polysilicon layer, the silicon wafer is sent into a furnace tube to perform phosphorus diffusion doping treatment on the polysilicon layer to form an n-type doped region. The silicon wafer after phosphorus diffusion doping treatment has a sheet resistance of 30-40Ω / sq, for example, 30Ω / sq.

[0039] In the above step 101, the back side of the silicon wafer is laser grooved to expose the n-type original silicon area, forming an n-type doped area and an n-type original silicon area arranged in an interdigitated manner, the n-type original silicon area is a p-type doping reserved area, that is, the n-type original silicon area is used for the subsequent formation of a p-type doped area; then the front polysilicon layer is removed by a wet method. In this step, the phosphosilicate glass coated on the front side can be removed by using a chain machine in a single-sided film removal method using an alkali solution to react with the phosphosilicate glass.

[0040] Optionally, when laser grooving the back of the silicon wafer, a laser is used to perform grooving using picosecond green light and laser marking. The laser marking speed is 32,000 to 38,000 mm / s, the power is 550 to 650 watts, and the frequency is 1,000 to 1,500 Hz. The width of the laser back groove is 250 to 300 microns and the depth is 1.5 to 2 microns.

[0041] For example, the laser performs grooving at a laser marking speed of 35,000 mm / s, a power of 600 watts, and a frequency of 1,200 Hz, and forms a laser groove with a width of 280 microns and a depth of 1.8 microns.

[0042] In the above step 102, the first region is within the n-type original silicon region and does not overlap with the edge of the n-type original silicon region; the boron aluminum paste is first printed in the first region by screen printing, and then dried and sintered after printing to form a boron aluminum coating on the first region.

[0043] In the above step 102, the first region is laser doped. Since the first region on the surface of the silicon wafer contains boron-aluminum slurry, the laser emitter can use this boron-rich boron-containing aluminum coating as a doping source, and emit laser pulses at high frequency to melt the surface of the silicon wafer, so that the boron and aluminum atoms in the boron-containing aluminum coating are pushed to the surface of the silicon wafer. After solidification, the doped boron atoms will quickly replace the position of silicon atoms, thereby achieving the purpose of diffusion and advancement of doped atoms, thereby forming a high-quality p-type doped region. The sheet resistance of the silicon wafer after laser doping is 50-60Ω / sq, for example, 55Ω / sq.

[0044] Optionally, the components of the boron aluminum paste include aluminum powder, silver powder, boron powder, glass powder, organic binder and organic additives.

[0045] Optionally, in the boron-aluminum paste, the mass percentage of the organic additive is 0.3-0.8%; the mass percentage of the boron powder is 0.5-1%; the mass percentage of the aluminum powder is 74-80%; the mass percentage of the organic binder is 16.7-24.2%; and the mass percentage of the glass powder is 1-1.5%.

[0046] Optionally, in the boron-aluminum paste, the boron powder includes elemental boron and / or boron-aluminum alloy.

[0047] Optionally, in the boron-aluminum paste, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.

[0048] Optionally, in the boron aluminum paste, the aluminum powder includes 85-90% by mass of micron spherical aluminum powder and 10-15% by mass of nano spherical aluminum powder.

[0049] Optionally, in the boron aluminum paste, the organic binder includes a high molecular polymer resin and an organic solvent;

[0050] The mass fraction of the high molecular weight polymer in the organic binder is 6 to 10%;

[0051] The mass fraction of the organic solvent in the organic binder is 90-94%.

[0052] Optionally, in the boron aluminum paste, the organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0053] Optionally, in the boron-aluminum paste, the glass powder includes Bi2O3 with a mass fraction of 15-25%, Al2O3 with a mass fraction of 6-10%, Pb2O5 with a mass fraction of 10-15%, ZnO with a mass fraction of 12-29%, Sb2O5 with a mass fraction of 15-25%, V2O5 with a mass fraction of 6-10%, TiO2 with a mass fraction of 9-25%, and BaO with a mass fraction of 10-20%.

[0054] Optionally, in the boron-aluminum paste, the boron powder is micron-grade boron powder.

[0055] Optionally, in one implementation, step 1001 is included before step 101, and step 1021 is included before step 102.

[0056] Step 1001: performing alkali polishing on the silicon wafer.

[0057] Step 1021, chain pickling and texturing treatment are performed on the silicon wafer after laser grooving.

[0058] In step 1001, the purpose of the alkali polishing treatment is to remove the surface damage from the original wafer cutting process; at the same time, the alkali polishing treatment also increases the surface area of ​​the battery cell to prepare for the increase of the junction area for diffusion.

[0059] In step 1021, before forming the passivation film layer and the anti-reflection film layer on both sides of the silicon wafer, chain pickling can be performed, and then double-sided texturing can be performed using a wet method.

[0060] Among them, chain pickling is to use pickling to remove metal impurities such as Al, Fe, Zn, Ni on the surface of the silicon wafer, as well as to remove metal hydroxides attached to the natural oxide film; and double-sided texturing can greatly reduce the reflectivity of the battery cell surface.

[0061] In practical applications, alkaline solution can be used to anisotropically etch single crystal silicon wafers to produce a velvet surface. The reaction principle is as follows: Si+2NaOH+H2O=Na2SiO3+2H2↑.

[0062] In essence, velvet is to etch a crystalline silicon wafer through anisotropic etching, and finally form a number of four side cones on the surface, that is, a "pyramid" structure. After the formation of this structure, when light is incident on a certain angle of the pyramid slope, the light will reflect the slope of another angle, forming two or more absorptions, thereby reducing the reflectivity of the silicon wafer surface, that is, the trapping effect. The better the size and uniformity of the "pyramid" structure, the more obvious the trapping effect, and the lower the surface emissivity of the silicon wafer.

[0063] Optionally, in another implementation, step 1002 is included before the above step 101 , and step 1022 is included before the above step 102 .

[0064] Step 1002, performing texturing treatment on the silicon wafer;

[0065] Step 1022: chain pickling and alkali polishing are performed on the laser grooved silicon wafer.

[0066] In this embodiment, a process of first texturing and then polishing is adopted to form a polished surface inside the laser groove, which can strengthen the contact between the slurry and the silicon wafer, thereby improving the efficiency of the battery and avoiding the problem that part of the slurry components are stuck because the slurry surface is too small, resulting in the slurry being unable to contact the bottom of the silicon.

[0067] In the method for preparing an N-type IBC battery provided by an embodiment of the present invention, the block size after alkali polishing is 9 to 11 microns, for example, 9 microns, 10 microns or 11 microns.

[0068] Optionally, the alkali polishing treatment is to perform wet alkali polishing on the original silicon wafer in the form of KOH+alkali polishing additive, wherein the mass percentage concentration of KOH is 1.5%, the alkali polishing additive is Tobang EP12V88, the processing time is 250-350s, and the processing temperature is 65-75°C.

[0069] Optionally, the alkali polishing treatment is to perform wet alkali polishing on the original silicon wafer by using KOH + alkali polishing additive, wherein, by volume, the alkali polishing solution includes 30 parts of concentrated KOH solution with a mass percentage concentration of 45%, 6 parts of alkali polishing additive and 380 parts of water, the treatment time is 340s, and the treatment temperature is 70°C.

[0070] Optionally, the chain pickling uses 3% by mass hydrochloric acid and 5% by mass hydrofluoric acid to clean the laser grooved silicon wafer, and the cleaning time is 30 seconds.

[0071] Optionally, the texturing treatment is a trough texturing treatment of the silicon wafer using KOH+texturing additive, wherein the mass percentage concentration of KOH is 1.2%, the texturing additive is EP12V58, the processing time is 620-670s, and the processing temperature is 77-82°C.

[0072] Optionally, the texturing treatment is a wet texturing treatment of the silicon wafer by using KOH + texturing additive, wherein, by volume, the texturing solution includes 15 parts of 45% concentrated KOH solution, 3 parts of texturing additive and 420 parts of water, the treatment time is 550s, and the treatment temperature is 80°C.

[0073] Optionally, in one implementation, before the above step 103, step 1031 is further included:

[0074] Step 1031 , performing acid washing on the silicon wafer after the laser doping treatment.

[0075] In this embodiment, the excess boron-containing aluminum coating and other impurities are removed by pickling.

[0076] Optionally, in a specific implementation, the above step 1031 specifically includes: cleaning the laser doped silicon wafer with 5% by mass HCl, and then treating the cleaned silicon wafer with 3% by mass HCl to ensure the cleanliness of the silicon wafer.

[0077] In the above step 103, an atomic layer deposition (ALD) process is used to plate a passivation layer on the entire front and back of the product to form field passivation; after the aluminum oxide film is formed, an anti-reflection film layer is first plated on the front of the battery, and then on the back, to further enhance the passivation effect of the battery cell.

[0078] Optionally, the passivation layer is an aluminum oxide film layer, that is, the aluminum oxide film layer is plated on the entire front surface and the entire back surface as the passivation layer.

[0079] Optionally, the anti-reflection film layer is a silicon nitride layer, that is, the anti-reflection film is formed by coating the entire front surface and the entire back surface with a silicon nitride layer; wherein the anti-reflection film includes multiple layers of silicon nitride layers, which can further enhance the anti-reflection effect.

[0080] In the above step 104, the silicon wafer with the anti-reflection film formed thereon is screen printed to prepare electrode grid lines.

[0081] Optionally, in one embodiment, the above step 104 specifically includes: printing silver-aluminum paste on a second area of ​​the anti-reflection film layer on the back side of the silicon wafer, the projection of the second area is within the p-type doping area, so as to form a positive gate line that is conductive to the p-type doping area; at the same time, it is also necessary to print silver paste on a third area of ​​the anti-reflection film layer on the back side, the projection of the third area is within the n-type doping area, so as to form a negative gate line separated from the positive gate line.

[0082] In this embodiment, the silver-aluminum paste is solidified by high-temperature sintering, and the silver-aluminum paste is used to burn through the anti-reflection film layer and the passivation layer in the second region to form a positive electrode grid line in contact with the p-type doped region. At the same time, the silver paste is solidified by high-temperature sintering, and the silver paste is used to burn through the anti-reflection film layer and the passivation layer in the third region to form a negative electrode grid line in contact with the n-type doped region, thereby eliminating the damage to the passivation layer caused by laser grooving, and the metallization grid line process can be completed to obtain an N-type IBC battery.

[0083] Optionally, in a specific embodiment, the components constituting the above-mentioned silver-aluminum paste include organic additives, silver powder, aluminum powder, boron-aluminum alloy powder, organic binder and glass powder.

[0084] Among them, silver powder and aluminum powder are the main components, aluminum powder is mainly used to replace the P+ emitter of the battery, and silver paste has good thermal conductivity, electrical conductivity and burn-through performance; glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; organic binder can ensure the overall bonding effect; organic additives can reduce the overall viscosity of the silver paste; because boron aluminum alloy powder can be mixed with metallic aluminum liquid, boron can be introduced into the silicon surface and diffused into the silicon for heavy doping, which is beneficial to improve the contact performance of the slurry and reduce the reaction contact area between aluminum and silicon; the above-mentioned silver aluminum paste can quickly form a good alloy with silicon under lower sintering temperature conditions, reduce the contact resistivity between the front silver aluminum grid and the battery, thereby improving the battery filling and battery efficiency.

[0085] Optionally, in a specific embodiment, in the above-mentioned silver-aluminum paste, the mass percentage of organic additives is 0.4-0.6%; the mass percentage of silver powder is 65-75%; the mass percentage of aluminum powder is 3-5%; the mass percentage of boron-aluminum alloy powder is 0.05-0.1%; the mass percentage of organic binder is 17.5-30.55%; and the mass percentage of glass powder is 1-1.8%.

[0086] For example, in the silver-aluminum paste, the mass fractions of the organic additive, silver powder, aluminum powder, boron-aluminum alloy powder, organic binder and glass powder are 0.4%, 77%, 3%, 0.1%, 17.7% and 1.8% respectively.

[0087] For example, in the silver-aluminum paste, the mass fractions of the organic additive, silver powder, aluminum powder, boron-aluminum alloy powder, organic binder and glass powder are 0.6%, 65%, 5%, 0.05%, 28.35% and 1%, respectively.

[0088] For example, in the silver-aluminum paste, the mass fractions of the organic additive, silver powder, aluminum powder, boron-aluminum alloy powder, organic binder and glass powder are 0.5%, 75%, 4%, 0.75%, 18.25% and 1.5%, respectively.

[0089] For example, in the silver-aluminum paste, the mass fractions of the organic additive, silver powder, aluminum powder, boron-aluminum alloy powder, organic binder and glass powder are 0.4%, 65%, 3%, 0.05%, 30.55% and 1%, respectively.

[0090] Optionally, in a specific embodiment, in the silver-aluminum paste, the aluminum powder includes a micron-grade aluminum powder with a mass fraction of 75-80% and a D50 of 5-6 μm, and a micron-grade aluminum powder with a mass fraction of 20-25% and a D50 of 9-10 μm; the silver powder includes a micron-grade silver powder with a mass fraction of 88-94% and a nano-grade silver powder with a mass fraction of 6-12%. Specifically, the aluminum powder includes a spherical aluminum powder with a purity of 3 nines and a mass fraction of 75-80% and a D50 of 5-6 μm, and a spherical aluminum powder with a purity of 3 nines and a mass fraction of 20-25% and a D50 of 9-10 μm. The silver powder is a micron-grade spherical silver powder with a purity of 3 nines and a mass fraction of 88-94% and a nano-grade spherical silver powder with a purity of 3 nines and a mass fraction of 6-12%. In the embodiment of the present invention, the above-mentioned silver powder is a micron-grade spherical silver powder with a purity of 3 nines. Among them, because there are gaps between micron-sized silver powders and gaps between micron-sized aluminum powders, the above-mentioned nano-sized spherical silver powder can just fill and penetrate into the gaps between the micron-sized ones.

[0091] The above-mentioned boron aluminum alloy powder is a micron-level boron aluminum alloy powder, which has the characteristics of high tap density, low oxygen content and high activity. By adding the micron-level boron aluminum alloy powder, the silver aluminum paste can quickly form a good alloy with silicon under lower sintering temperature conditions, thereby reducing the contact resistivity between the front silver aluminum fine grid and the battery.

[0092] Optionally, in a specific embodiment, in the silver aluminum paste, the organic additive includes at least one of a silane coupling agent, lauryl phosphate, silicone oil, and a dibasic acid ester.

[0093] Optionally, in a specific embodiment, in the silver-aluminum paste, the organic binder includes a polymer resin and an organic solvent; wherein the polymer resin is dissolved in the organic solvent, so that the organic solvent can be used as an organic binder, that is, the paste plays a role in bonding powders after drying.

[0094] Optionally, in a specific embodiment, in the silver-aluminum paste, the mass fraction of the high molecular polymer in the organic binder is 9-15%; the mass fraction of the organic solvent in the organic binder is 85-91%.

[0095] Optionally, in a specific embodiment, in the silver aluminum paste, the high molecular weight polymer is one or more of ethyl cellulose-N20, ethyl cellulose N-50, and ethyl cellulose-N100;

[0096] The organic solvent comprises at least four of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.

[0097] Optionally, in a specific embodiment, in the silver-aluminum paste, the glass powder is obtained by sintering and crushing 20 to 25 parts of Bi2O3, 6 to 8 parts of Al2O3, 10 to 12 parts of SiO2, 5 to 29 parts of ZnO, 15 to 20 parts of Sb2O5, 5 to 20 parts of BaO, 5 to 8 parts of B2O3, and 15 to 22 parts of TeO3, by mass, and the D50 of the glass powder is 1.2 to 2 μm. If D50 is less than 1.2 μm, the glass activity is too large, and if D50 is greater than 2 μm, the glass activity is too small.

[0098] Among them, Bi2O3 is the main network structure, ZnO can break the network structure and promote glass crystallization, Al2O3 can adjust glass stability and increase viscosity; SiO2 is used for glass network formation, promoting glass stability and increasing glass melting point; Sb2O5 is used for clarification and uniformity of glass liquid; BaO is used for local crystallization; B2O3 is a network body; and TeO3 reduces the glass formation temperature. The D50 of glass powder is 1.5~2μm.

[0099] Optionally, in the step 104, the high temperature sintering temperature is 750-800°C, for example, 750°C, 766°C or 800°C.

[0100] The present invention also provides an N-type IBC battery, wherein the battery is prepared by the above-mentioned preparation method of the N-type IBC battery.

[0101] The present invention is described in detail below by way of examples.

[0102] Example 1

[0103] The boron aluminum paste is composed of 0.5 parts of organic additives, 0.8 parts of boron powder, 76 parts of aluminum powder, 21.5 parts of organic binder and 1.2 parts of glass powder by mass;

[0104] Among them, the above-mentioned organic additive is a silane coupling agent; the boron powder is a micron-grade elemental boron with a purity of 2 9s; the aluminum powder includes a micron-grade spherical aluminum powder with a purity of 3 9s and a mass fraction of 88%, and a nano-spherical aluminum powder with a purity of 3 9s and a mass fraction of 12%; the organic binder includes ethyl cellulose-N100 with a mass fraction of 6% and an organic solvent with a mass fraction of 94%, and the organic solvent is composed of benzyl alcohol, pine oil, butyl carbitol, butyl carbitol acetate and Span 85; the glass powder is obtained by sintering and crushing 17% Bi2O3, 8% Al2O3, 12% Pb2O5, 15% ZnO, 20% Sb2O5, 6% V2O5, 12% TiO2, and 10% BaO with a mass percentage, and its D50 is 1.5-2μm.

[0105] (1) An N-type silicon wafer of 182*182 is subjected to alkali polishing treatment to form a 9-11 μm square on the surface; wherein, the original silicon wafer is subjected to wet alkali polishing by using KOH+alkali polishing additive, wherein, by volume, the alkali polishing solution comprises 30 parts of a concentrated KOH solution with a mass percentage concentration of 45%, 6 parts of an alkali polishing additive and 380 parts of water, the treatment time is 340 seconds, and the treatment temperature is 70°C;

[0106] (2) After forming a silicon oxide layer and a polysilicon layer on the back of an N-type silicon wafer, phosphorus diffusion doping is performed on the back polysilicon layer; the square resistance after phosphorus diffusion is 35Ω / sq, and the junction depth of ECV is 0.9μm;

[0107] (3) laser grooving the back side of the phosphorus-doped N-type silicon wafer to form interdigitated n-type doped regions and n-type original silicon regions;

[0108] (4) Taking the silicon wafer after laser grooving, wet texturing treatment is performed on the silicon wafer by using KOH + texturing additive, wherein the texturing solution includes 15 parts by volume of a concentrated KOH solution with a mass percentage concentration of 45%, 3 parts of a texturing additive and 420 parts of water, the treatment time is 550 seconds, and the treatment temperature is 80°C;

[0109] (5) After removing the front polysilicon layer, printing the boron aluminum paste in the first region of the n-type original silicon region by screen printing, drying and sintering after printing to form a boron aluminum coating on the first region, and then performing laser doping treatment on the first region; the sheet resistance after laser doping treatment is 55Ω / sq;

[0110] (6) After the laser doping treatment, the silicon wafer is cleaned with 5% and 3% hydrochloric acid in sequence, and a passivation film layer, a front anti-reflection film layer, and a back anti-reflection film layer are formed in sequence on the back of the silicon wafer, and then a silver aluminum paste is printed on a second area of ​​the back anti-reflection film layer of the silicon wafer, and the projection of the second area is within the range of the first area; at the same time, a silver paste is printed on a third area of ​​the back anti-reflection film layer, and the projection of the third area is within the range of the n-type doping area;

[0111] (7) The N-type silicon wafer is subjected to high-temperature sintering to obtain an N-type IBC battery, and the peak sintering temperature is 768°C.

[0112] After sintering, the electrical properties tested were: open circuit voltage of 728.4 mV and photoelectric conversion efficiency of 25.34%.

[0113] Comparative Example 1

[0114] (1) An N-type silicon wafer of 182*182 is subjected to alkali polishing treatment to form a 9-11 μm square on the surface; wherein, the original silicon wafer is subjected to wet alkali polishing by using KOH+alkali polishing additive, wherein, by volume, the alkali polishing solution comprises 30 parts of a concentrated KOH solution with a mass percentage concentration of 45%, 6 parts of an alkali polishing additive and 380 parts of water, the treatment time is 340 seconds, and the treatment temperature is 70°C;

[0115] (2) Perform tubular boron diffusion on the back of the N-type silicon wafer to form a p-type doped region; the square resistance after phosphorus diffusion is 35Ω / sq, and the ECV junction depth is 0.9μm;

[0116] (3) After forming a silicon oxide layer and a polysilicon layer on the back of the N-type silicon wafer, phosphorus diffusion doping is performed on the back polysilicon layer; the square resistance after phosphorus diffusion is 35Ω / sq, and the ECV junction depth is 0.9μm;

[0117] (3) laser grooving the back of the phosphorus-doped P-type silicon wafer to form interdigitated n-type doped regions and p-type original silicon regions;

[0118] (4) Taking the silicon wafer after laser grooving, wet texturing treatment is performed on the silicon wafer by using KOH + texturing additive, wherein the texturing solution includes 15 parts by volume of a concentrated KOH solution with a mass percentage concentration of 45%, 3 parts of a texturing additive and 420 parts of water, the treatment time is 550 seconds, and the treatment temperature is 80°C;

[0119] (5) after removing the front polysilicon layer, forming a passivation film layer, a front anti-reflection film layer, and a back anti-reflection film layer on the back of the silicon wafer in sequence, printing silver-aluminum paste on a second region of the anti-reflection film layer on the back of the silicon wafer, wherein the projection of the second region is within the range of the first region; and at the same time, printing silver paste on a third region of the back anti-reflection film layer, wherein the projection of the third region is within the range of the n-type doping region;

[0120] (6) The N-type silicon wafer is subjected to high-temperature sintering to obtain an N-type IBC battery, and the peak sintering temperature is 768°C.

[0121] After sintering, the electrical properties tested were: open circuit voltage of 724.6 mV and photoelectric conversion efficiency of 25.12%.

[0122] To summarize, in this embodiment, by forming a boron-aluminum coating on the first area of ​​the n-type original silicon area and performing laser doping treatment, the n-type original silicon area can be doped with high-concentration boron to form a p-type doped area, thereby avoiding the side effects caused by the doping method of the traditional tubular boron source, and the photoelectric conversion efficiency can be improved by 0.3%, thereby solving the problem that the formation method of the p-type doped area of ​​the existing N-type IBC battery is complex and has many side effects, and is easy to affect the photoelectric conversion efficiency of the battery.

[0123] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.

[0124] The above is a detailed introduction to an N-type IBC battery and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing an N-type IBC battery, characterized in that: include: After forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back of an N-type silicon wafer, laser grooves are formed on the back of the silicon wafer to form an n-type doped region and an n-type original silicon region arranged in an interdigitated manner; forming a boron-aluminum coating on a first region within the n-type original silicon region, and then performing a laser doping process on the first region; After laser doping treatment, a passivation film layer and an anti-reflection film layer are formed on both sides of the silicon wafer; After forming the anti-reflection film layer, a positive electrode grid line in contact with the first region and a negative electrode grid line in contact with the n-type doped region are formed on the back of the silicon wafer to manufacture an N-type IBC battery.

2. The preparation method according to claim 1, characterized in that: The laser marking speed of the laser grooving is 32000-38000 mm / sec, the power is 550-650 watts, and the frequency is 1000-1500 Hz.

3. The preparation method according to claim 1, characterized in that: A silicon oxide layer and a phosphorus-doped polysilicon layer are sequentially formed on the back of the N-type silicon wafer, including: A silicon oxide layer and a polysilicon layer are sequentially formed on the back of an N-type silicon wafer by low-pressure vapor deposition, and then the polysilicon layer is subjected to phosphorus diffusion doping treatment.

4. The preparation method according to claim 3, characterized in that: The sheet resistance of the silicon wafer after phosphorus diffusion doping treatment is 30-40Ω / sq, and the sheet resistance of the silicon wafer after laser doping treatment is 50-60Ω / sq.

5. The preparation method according to claim 1, characterized in that: The passivation layer is an aluminum oxide layer, and the anti-reflection film layer is a silicon nitride layer.

6. The preparation method according to claim 1, characterized in that: Before sequentially forming a silicon oxide layer and a phosphorus-doped polysilicon layer on the back side of the N-type silicon wafer, the method further comprises: performing alkali polishing on the silicon wafer; Before forming the boron-containing aluminum coating on the first region within the n-type native silicon region, the method further includes: The silicon wafers after laser grooving are chain pickled and texturing treated.

7. The preparation method according to claim 6, characterized in that: The block size after alkali polishing is 9 to 11 microns.

8. The preparation method according to claim 1, characterized in that: Before forming the passivation film layer and the anti-reflection film layer on both sides of the silicon wafer, the method further includes: The silicon wafer after laser doping is pickled.

9. The preparation method according to claim 1, characterized in that: The width of the laser groove is 250 to 300 microns and the depth is 1.5 to 2 microns.

10. An N-type IBC battery, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Cited By

  • Solar cell and preparation method thereof

    CN119866103A